New species and records of the Rhamphomyia subgenus Holoclera (Diptera, Empididae) from the Palaearctic Region - Shamshev, Igor V.; Barták, Miroslav (Zootaxa, 2024)
New data on the Palaearctic subgenus Holoclera Schiner of dance flies of the genus Rhamphomyia Meigen (Diptera: Empididae) are reported. Three new species are described: Rhamphomyia (Holoclera) richterae sp. nov. (Russia: Adygea, Krasnodarskiy Territory), R. (H.) stepankubiki sp. nov. (Armenia, Turkey), and R. (H.) vikhrevi sp. nov. (Morocco). New extensive distributional data are provided, especially for the Eastern Palaearctic. The subgenus has been found to have a trans-Palaearctic distribution. However, only five of 23 named species, which this group comprises, occur beyond the Urals. The distribution of R. (H.) culicina (Fallén) and R. (H.) sciarina (Fallén) (both R. (H.) flava group) extends to the east as far as the Russian Far East (Magadanskaya and Amurskaya Provinces, respectively). Amongst the species of the R. (H.) nigripennis group, R. (H.) nigripennis (Fabricius) has the broadest distribution extending to the east as far as Krasnoyarskiy Territory of Russia (Eastern Siberia). In addition, R. (H.) lamellata Collin and R. (H.) caliginosa Collin were recorded from Western Siberia and Kyrgyzstan, respectively. The latter is the first record of R. (Holoclera) from Middle Asia. Only one species (R. (H.) sciarina) occurs in the subarctic regions of Asia (Taymyr Peninsula). The following records are new for the states noted: R. (H.) helvetica Barták & Kubík (France and Germany), R. (H.) lamellata (Estonia, Finland and Ukraine), R. (H.) trigemina Oldenberg (Estonia and Sweden), R. (H.) umbripennis Meigen (Armenia), R. (H.) variabilis (Fallén) (Ukraine). An updated key to species of Holoclera from the Palaearctic Region is provided.